FILARIASIS PRESENTING AS BONE MARROW SUPPRESSION - Singh, Anup; Kumari, Sarita (Journal of Ayub Medical College Abbottabad, 2016)
Lymphatic filariasis is caused by most commonly Wuchereria bancrofti inIndia. The diagnosis is made by demonstration of microfilariae in the peripheral blood, body fluids, fine needle aspirates and in bronchial brushings. Presence of microfilariae in the bone marrow is unusual and not been reported frequently. We are reporting here a case of a young male who had pancytopenia and was found to have microfilariae in the bone marrow. Keywords: Microfilariae; Pancytopenia; Bone Marrow